Severity-adjusted evaluation of liver transplantation on health outcomes in urea cycle disorders - Posset, Roland; Garbade, Sven; Gleich, Florian; Scharré, Svenja; Okun, Jürgen G.; Gropman, Andrea L.; Nagamani, Sandesh C. S.; Druck, Ann-Catrin; Epp, Friederike; Hoffmann, Georg F.; Kölker, Stefan; Zielonka, Matthias (Genetics in medicine, 2024)
Purpose - Liver transplantation (LTx) is performed in individuals with urea cycle disorders when medical management (MM) insufficiently prevents the occurrence of hyperammonemic events. However, there is a paucity of systematic analyses on the effects of LTx on health-related outcome parameters compared to individuals with comparable severity who are medically managed. - Methods - We investigated the effects of LTx and MM on validated health-related outcome parameters, including the metabolic disease course, linear growth, and neurocognitive outcomes. Individuals were stratified into “severe” and “attenuated” categories based on the genotype-specific and validated in vitro enzyme activity. - Results - LTx enabled metabolic stability by prevention of further hyperammonemic events after transplantation and was associated with a more favorable growth outcome compared with individuals remaining under MM. However, neurocognitive outcome in individuals with LTx did not differ from the medically managed counterparts as reflected by the frequency of motor abnormality and cognitive standard deviation score at last observation. - Conclusion - Whereas LTx enabled metabolic stability without further need of protein restriction or nitrogen-scavenging therapy and was associated with a more favorable growth outcome, LTx - as currently performed - was not associated with improved neurocognitive outcomes compared with long-term MM in the investigated urea cycle disorders.
Online verfügbar: 3. Dezember 2023, Artikelversion: 13. Februar 2024
Gesehen am 31.07.2024